The New Keynesian business cycle achievements and challenges - Saroliya, Gaurav (2018)
The New-Keynesian (NK) business cycle model has presented itself as a potential “workhorse” model for business cycle analysis. This paper seeks to assess afresh the performance of the baseline NK model and its various extensions. The main theme of the paper is that although the dynamic NK literature has secured a robust defence to criticism arising, inter alia, on account of lack of microfoundations, it still has a long way to go in terms of providing a fully satisfactory model of the business cycle. In this regard, it is conjectured that explicitly accounting for the role of heterogeneity in business- cycle dynamics could lead towards a viable solution.